Main effects of retinol palmitate on skin structures and the technology of its use in dermatological practice - Stanislava Yu. Petrova; Vera I. Albanova; Konstantin V. Nozdrin; Konstantin S. Guzev (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Vitamin A and its synthetic analogues are used in the treatment of numerous skin diseases. The main genomic effects of the natural form of vitamin A (retinol palmitate) are associated with its active metabolite all-trans-retinoic acid and are compensated by several restrictive mechanisms. Numerous studies have proved that retinol stimulates the proliferation of keratinocytes of the basal layer of the epidermis and endothelial cells, and also activates dermal fibroblasts to synthesize proteins of the extracellular matrix of the dermis. As a result, the thickening the epidermis, increases the mechanical strength of the skin and the hydrating ability of the dermis, angiogenesis increase. The ability of retinol to enhance the adhesion of endothelial cells and leukocytes, regulate the processes of keratinization and sebum secretion was found. Vitamin A is also a powerful antioxidant. Retinol palmitate is used as the main or auxiliary drug for the treatment of a wide range of dermatoses. The principle of application is based on clinical studies and confirmed by existing experimental data. In the treatment, the following algorithm is followed. If retinol palmitate is necessary to improve epithelialization and strengthen the epidermal barrier, medium therapeutic doses should be used. For the treatment of disorders of keratinization processes, depending on the severity of the pathological condition, medium and high therapeutic doses of the drug are used. Violation of the processes of sebum secretion and severe hyperkeratosis respond better to treatment at high therapeutic doses. It should be noted that many skins clinical manifestations mostly regress under the action of vitamin A in doses that do not lead to the appearance of signs of toxicity of the drug.